Analysis of the Subject-Verb Agreement Ability among Indonesian English Major Students as EFL Learners - Alican Mendez Pandapatan (Journal of English Language Studies, 2020)
Subject-verb agreement is relevant in determining one's grammatical ability. The study examines the 70 English major students of UNTIRTA through a questionnaire. They are in semester four or second-year students of the academic year 2019-2020. A percentage result per item has been the indicator of students' knowledge on the five categories namely; the basics, impersonal subjects, quantities, exceptions, and main and auxiliary verbs. The verification of the incorrect response is through the short-written production of students' composition. Not only nouns that used as subjects but also other parts of speech and unit blocks of syntax.  It reveals that a lot of students commit mistakes in choosing the right verb that agrees to the subject. This finding implies interference of first language and second language as parcel in mastering the subject-verb agreement which results to struggle and confusion among the learners. Lack of emphasis on grammar practice in writing is also a reason in applying the rules especially the basics. Moreover, cultural difference is a barrier in interpreting the sentences wherein the learners’ vocabulary is limited. Suggested instructional strategy is a regular practice of the rules in the form of drill.